EP 125. Inverse bimanual visuomotor coordination is predicted by specific executive functions. Issue 9 (September 2016) - Gooßes, M.; Eickhoff, S.B.; Langner, R.
Abstract : Introduction: Bimanual visuomotor coordination often seems effortless in many everyday activities (e.g., dressing, eating, driving). Nevertheless, coordinating different but interdependent voluntary movements of each hand to achieve a common goal can be rather difficult, as the interaction of the two movements needs to be integrated with perceptual feedback in a top-down fashion. Aim: To examine to what degree this integration is predicted by different facets of motor control and executive functioning. Methods: Bimanual visuomotor coordination was assessed in 18 young (mean age: 26.0 yrs.) and 20 older (59.1 yrs.) adults using the Inverse Two-Hand Coordination Test (Schuhfried Test System), a computerized task that requires participants to steer a small virtual ball along an on-screen path. Ball movement is controlled via two joysticks: a left-hand one for horizontal, a right-hand one for vertical motion. Note that in the inverse version used here, ball movement direction is inverted relative to the hand movement (e.g., a joystick movement to the left will move the ball to the right). Further tests assessed simple (i.e. non-inverse) two-hand visuomotor coordination, one-hand visuomotor coordination (Trail Making Test [TMT-A and -B]), one-hand motor control (Motor Performance Series), inhibitory control (Go/Nogo task), divided attention, and cognitive flexibility (difference between TMT-B and -A). To identify potential predictors of inverse bimanual coordination (IBC), we compared performance in all tests between those older participants who were able ( n  = 13) and those who were unable ( n  = 7) to perform the IBC task. Test scores showing a significant group difference were included in a binary logistic regression analysis to test how well they predict group affiliation (IBC success vs. failure). Linear regression analysis examined how well these scores explain different aspects of IBC performance across all (young and old) successful IBC performers ( n  = 31). Results: Significantly decreased performance in the IBC failure subgroup was observed for TMT-A and TMT-B, Go/Nogo task (mean reaction time), and simple bimanual coordination (average speed and error duration). In a logistic regression model, these 5 scores predicted group affiliation with 88.9% accuracy. In a linear regression, all 5 scores significantly contributed to predicting IBC performance, jointly explaining 40% of variance in speed, 50% in error duration, and 95% in percentage error duration. Discussion: Our results show that specific aspects of executive functioning, rather than motor skills per se, explain IBC performance across age. This indicates that the limitations in older adults to perform the task may arise from cognitive aspects of this complex "motor task" (e.g. intentional movement de-coupling, input–output coordinate transformation, error monitoring). We suggest that these parallel cognitive processing demands lead to mutual interference and eventually, reflecting well-known multitasking deficits in the elderly, may lead to a complete breakdown of complex visuomotor coordination.